(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
We conducted this research because many young people and adults today are growing fonder of junk foods and getting less familiar with vegetables. This study aims to provide people with another alternative way to increase the consumption of Banana hearts by turning them into a delicious and healthy patty. We also aim to introduce a new way to enjoy the Banana Heart vegetable in the form of a patty. We also aim to increase the consumption of Banana heart vegetables. This research employs a quantitative descriptive research design utilizing personal survey-type questionnaires to gather information about the acceptability of banana patty as an alternative beef patty perceived by, HE Student According to Fluet (2021), descriptive research is a definitive quantitative research method that is commonly used to evaluate certain hypotheses and characterize traits or functions. Thus, this design will be used since the main objective of this research is to know the acceptability of banana patty as an alternative beef patty perceived by HE Students. The student’s findings in the assessment of the summary of the table is a composite of the weighted mean of 4.46 in nutritional food, financial 4.06 and avoid fat deposit 4.16, Taste 4.16 presentation total composite weighted mean, which is strongly agreed. When we had the results from our surveys, which determine if Banana heart patty is accepted by the grade 12 home economics students in Bestlink College of the Philippines A.Y 2021-2022 to eat, the mean score was interpreted to be acceptable to be eaten by the respondents. The respondents also accepted that eating a Banana heart patty will gain healthy benefits such as Vitamin C and Potassium, which help your body heal, build muscle, and boost your immune system.